The relationship of obstructive sleep apnea and cardiovascular diseases from the perspective of evidence-based medicine. Part 1 - М. V. Agaltsov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2020)
The results of prospective studies, meta-analyzes and systematic reviews on the associations of obstructive sleep apnea (OSA) with various cardiovascular diseases (CVD) were analyzed. Currently, the mechanisms related to high prevalence of breathing-related sleep disorders among population of economically developed countries are clear, and an increase in the number of OSA patients has been shown. The relationship between OSA and CVD has been widely confirmed in large cohort studies. The first review part discusses the relationship of hypertension (HTN) and various heart arrhythmias (atrial fibrillation (AF), bradyarrhythmias, premature ventricular contraction, sudden death during sleep) with breathing-related sleep disorders. These groups of cardiovascular disorders currently show the most proven relationship with sleep apnea. In addition to cross-sectional studies indicating the high prevalence of OSA in patients with HTN and AF, some observational studies indicate an increase in the number of patients with HTN and paroxysmal AF with history of untreated sleep apnea. An analysis of the current issues of OSA phenotypes (in particular, REM-related OSA in hypertensive patients) as the most unfavorable cardiovascular factors is carried out.